Emerging Lung Cancer Therapeutic Targets Based on the Pathogenesis of Bone Metastases. (13th August 2014) - Oyewumi, Moses O.; Alazizi, Adnan; Wehrung, Daniel; Manochakian, Rami; Safadi, Fayez F.
Abstract : Lung cancer is the second most common cancer and the leading cause of cancer related mortality in both men and women. Each year, more people die of lung cancer than of colon, breast, and prostate cancers combined. It is widely accepted that tumor metastasis is a formidable barrier to effective treatment of lung cancer. The bone is one of the frequent metastatic sites for lung cancer occurring in a large number of patients. Bone metastases can cause a wide range of symptoms that could impair quality of life of lung cancer patients and shorten their survival. We strongly believe that molecular targets (tumor-related and bone microenvironment based) that have been implicated in lung cancer bone metastases hold great promise in lung cancer therapeutics. Thus, this paper discusses some of the emerging molecular targets that have provided insights into the cascade of metastases in lung cancer with the focus on bone invasion. It is anticipated that the information gathered might be useful in future efforts of optimizing lung cancer treatment strategies.